2015
DOI: 10.1620/tjem.237.163
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol Inhibits Constitutive and Inducible STAT3 Signaling via PU.1-Induced SHP1 Expression in Acute Myeloid Leukemia Cells

Abstract: Constitutive and inducible activation of signal transducer and activator of transcription 3 (STAT3) signaling facilitates the carcinogenesis in most human cancers including acute myeloid leukemia (AML). Negative regulators, such as protein tyrosine phosphatases SHP1, inhibit the activated STAT3 signaling. In this study, we investigated the effect of honokiol (HNK), a constituent of Magnolia officinalis, on the STAT3 signaling. STAT3 signaling and SHP1 expression were measured by quantitative real-time PCR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…Similarly, honokiol also induces apoptosis through the suppression of JAK2/STAT3, Akt and Erk signalling pathways in human oral squamous cell carcinoma (SAS and OCEM-1) cell lines [95]. Similar effect was observed in oral cancer cells where honokiol suppressed JAK2/STAT3 activation and, inhibited IL-6-mediated cell migration [95,183]. Furthermore, another study indicated that honokiol induces apoptosis in human glioblastoma cell line U87 through suppressing the phosphorylation of STAT3 (Tyr705), down-regulating survivin, and upregulating cleaved caspase-3 expression [98].…”
Section: Signal Transducers and Activators Of Transcription (Stats)mentioning
confidence: 75%
See 1 more Smart Citation
“…Similarly, honokiol also induces apoptosis through the suppression of JAK2/STAT3, Akt and Erk signalling pathways in human oral squamous cell carcinoma (SAS and OCEM-1) cell lines [95]. Similar effect was observed in oral cancer cells where honokiol suppressed JAK2/STAT3 activation and, inhibited IL-6-mediated cell migration [95,183]. Furthermore, another study indicated that honokiol induces apoptosis in human glioblastoma cell line U87 through suppressing the phosphorylation of STAT3 (Tyr705), down-regulating survivin, and upregulating cleaved caspase-3 expression [98].…”
Section: Signal Transducers and Activators Of Transcription (Stats)mentioning
confidence: 75%
“…In summary, both microneedles and chemical enhancers can improve the absorption of honokiol through the skin. Directly applying honokiol on mammary papilla is a potential administration route which can increase localized delivery into breast tissue [183].…”
Section: Metabolism Bioavailability and Pharmacological Relevance Omentioning
confidence: 99%
“…AML is a kind of hematological malignancies characterized by the infiltration of blasts to the bone marrow, blood, and other tissues. 19,30 Constitutive activation of STAT3 has a critical impact on the carcinogenesis, 15 principle of turmeric) as a phytochemical inhibits proliferation in different types of cancer cells via targeting multiple cellular signaling pathways such as NF-kB, the mitogen-activated protein kinase, Wnt, PI3K/AKT/mTOR and Notch-mediated signaling pathways. 31,32 During the last few years, several studies have investigated the potential impact of CUR (alone or in combination with other anticancer agents) on cancer stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Inhibition of STAT3 signaling cascades causes cell apoptosis and ultimately leukemia remission. 14,15 BCL-XL is a member of BCL-2 families. 16 BCL-XL has an anti-apoptotic effect, controlled by several mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Constitutive and inducible activation of STAT3 signaling promotes carcinogenesis in many human cancers such as acute myeloid leukemia. Negative regulators, such as protein tyrosine phosphatase SHP-1, may suppress the activated STAT3 signaling [20]. Additionally, 3 phosphatases, TC45, SHP-1 and SHP-2, are the primary contributory enzymes of UVB-mediated STAT3 dephosphorylation, and this may be a protective mechanism against UV skin carcinogenesis [21].…”
Section: Discussionmentioning
confidence: 99%